The Conflict in Cabo Delgado: impact in Mozambique foreign affairs and the reshaping of the bilateral agreements - Costa, C. M.; Santos, AMS (China, Guinea-Bissau, Mozambique and São Tomé and Príncipe: From sporadic bilateral exchanges to a comprehensive multilateral platform, 2022)
The conflict in Cabo Delgado results from the degradation of power relations in the Province of Cabo Delgado. The feeling of abandonment and withdrawal from power by the local population generated social contestation to government decisions. Simultaneously, the Islamic extremist movements approached the Mozambican frontiers and deepened their influence and attraction towards youngsters, exposing them to extremist ideas and training them in military skills. The outcome of this situation was an armed conflict that progressively affected local populations and the economic environment. Cabo Delgado is resource-rich and attracted foreign investment to the region. With the armed conflict situation, international agreements and even foreign policy and bilateral relations were affected. This chapter explores the impact this conflict had in the reshaping of the foreign policy and bilateral relations of Mozambique with other countries, mainly the People’s Republic of China, and how it affected the international economic agreements.